Species composition, distribution and abundance of trees in a one-hectare plot in Taklong Island, Guimaras - Contreras, Ruth
A one-hectare plot adjacent to the UPV Marine Biological Station was chosen as the study area. The local names of each tree in the plot was identified. GBH and height of trees were also noted. From the data gathered, the Basal Area, Index of Dominance, Index of Diversity and Frequency were computed. In addition, the distribution of trees in relation to its oil profile and nutrients was noted. One thousand eighty seven trees were found in the one-hectare plot comprised of forty-five and one unknown species of tree. The Top five most occuring species in the plot are Tabong, Ipil-ipil, Molave, Kusol and Sibukaw. The computed value of the Index Dominance is lowe than the computed value of the Index of Diversity, indicating that the area is diverse and that there are no dominating species. The distribution of trees in the one-hectare plot are random and is not affected by the soil nutrients.